Freshwater Transport in the Scotian Shelf and Its Impacts on the Gulf of Maine Salinity. Issue 1 (24th January 2022) - Wang, Zhengui; Li, Denghui; Xue, Huijie; Thomas, Andrew C.; Zhang, Yinglong J.; Chai, Fei
Abstract: A 3D unstructured‐grid ocean circulation model covering the continental shelf and coastal seas around New England is used to investigate freshwater transport (FWT) on the Scotian Shelf (SS) and its impact on the salinity in the Gulf of Maine (GoME). The model was first validated using observed elevation, velocity, temperature, and salinity at multiple locations, demonstrating generally high model skills. Intraseasonal variabilities of freshwater fluxes in 2017 and 2018 were then analyzed across different transects around SS and Browns Bank (BB). These indicated that the flow pattern in SS during 2017 was consistent with previous understanding: low salinity water flows southwestward along the shelf and turns into the GoME around BB. However, in 2018, most of the low salinity water did not enter the GoME, but was transported to the open ocean. The most striking difference occurred early in the year when the FWT, normally at its maximum, was practically stopped by an anticyclonic eddy impinging upon the shelf break near the western end of SS. Then in March, in contrast to the prevailing eastward wind, two southwestward wind events occurred that induced an excessive amount of FWT in SS. We further showed that when anticyclonic eddies impinge on the shelf break, the typical geostrophic balance associated with southwestward flow is interrupted, and a new geostrophic balance is established with the directions of pressure gradient force and flow reversed. The influence from anticyclonic eddies explains the abnormally low FWT in SS and higher GoME salinity in 2018. Plain Language Summary: In this research, we built an ocean circulation model around New England area and verified the model performance in capturing the variations of water level, velocity, temperature, and salinity. We used this model to analyze the movement of freshwater content that is contained in the seawater on the Scotian Shelf (SS) in 2017–2018, and studied its influence on the salinity in the downstream Gulf of Maine (GoME). The model shows that in 2017 the freshwater flew southwestward along the SS and then entered into the GoME, while in 2018 most of the freshwater did not enter the GoME, but went to the open ocean. The absence of freshwater input from the SS was caused by frequent anticyclonic eddies around the SS, which resulted in higher salinity in the GoME. In addition, we found that the southwestward wind can significantly increase the freshwater flow on the SS. Key Points: NorthEast Shelf Seas model was constructed and validated to study freshwater transport (FWT) in the Scotian Shelf (SS) Southwestward wind can significantly increase the FWT in the SS Anticyclonic eddies blocked the FWT in the SS resulting in higher Gulf of Maine salinity in 2018